The Life of Breath in Literature, Culture and Medicine Classical to Contemporary - Fuller, David; Saunders, Corinne; Macnaughton, Jane (Palgrave Studies in Literature, Science and Medicine, 2021)
This open access book studies breath and breathing in literature and culture and provides crucial insights into the history of medicine, health and the emotions, the foundations of beliefs concerning body, spirit and world, the connections between breath and creativity and the phenomenology of breath and breathlessness. Contributions span the classical, medieval, early modern, Romantic, Victorian, modern and contemporary periods, drawing on medical writings, philosophy, theology and the visual arts as well as on literary, historical and cultural studies. The collection illustrates the complex significance and symbolic power of breath and breathlessness across time: breath is written deeply into ideas of nature, spirituality, emotion, creativity and being, and is inextricable from notions of consciousness, spirit, inspiration, voice, feeling, freedom and movement. The volume also demonstrates the long-standing connections between breath and place, politics and aesthetics, illuminating both contrasts and continuities.